2007
DOI: 10.1007/s00382-007-0231-3
|View full text |Cite
|
Sign up to set email alerts
|

Climatic changes in Eurasia and Africa at the last glacial maximum and mid-Holocene: reconstruction from pollen data using inverse vegetation modelling

Abstract: In order to improve the reliability of climate reconstruction, especially the climatologies outside the modern observed climate space, an improved inverse vegetation model using a recent version of BIOME4 has been designed to quantitatively reconstruct past climates, based on pollen biome scores from the BIOME6000 project. The method has been validated with surface pollen spectra from Eurasia and Africa, and applied to palaeoclimate reconstruction. At 6 cal ka BP (calendar years), the climate was generally wet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

47
269
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 260 publications
(322 citation statements)
references
References 64 publications
47
269
6
Order By: Relevance
“…The reconstructed anomalies under low CO 2 concentration are not significantly different from the reconstructed anomalies under high CO 2 concentration. Wu et al (2007a) found a clear bias for winter temperature, i.e. about 10 • C colder under higher CO 2 , but nothing for summer temperature.…”
Section: Application B: Eurasia and Africa At The Lgmmentioning
confidence: 84%
See 3 more Smart Citations
“…The reconstructed anomalies under low CO 2 concentration are not significantly different from the reconstructed anomalies under high CO 2 concentration. Wu et al (2007a) found a clear bias for winter temperature, i.e. about 10 • C colder under higher CO 2 , but nothing for summer temperature.…”
Section: Application B: Eurasia and Africa At The Lgmmentioning
confidence: 84%
“…This bias reaches 3 • C in southernmost sites but not more than 1 • C in nothernmost ones, meaning that CO 2 becomes more limiting than temperature far away from the ice cap. Wu et al (2007a) have improved the method. First BIOME3 has been replaced by BIOME4 .…”
Section: Application A: Europe At the Last Glacial Maximummentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, the Last Glacial Maximum (LGM) is particularly interesting since it concerns a significantly different climate compared to present and since great efforts have been put and are still on the way concerning reconstructions of oceanic conditions (CLIMAP 1981;Mix et al 2001;Kucera et al 2005) and of continental climate (e.g. Wu et al 2007). The comparison between the different models is also very instructive and helps evaluate the consistency of model results.…”
Section: Context and Aimsmentioning
confidence: 99%